SURVEI KEPUASAN PELAYANAN BADAN KEPEGAWAIAN DAERAH DAN DIKLAT KABUPATEN PANDEGLANG TAHUN 2017 - Dirlanudin Dirlanudin; Agus Sjafari Agus Sjafari; Atik Atiatun Nafisah Atik Atiatun Nafisah; Ade Hadiono Ade Hadiono (LPPM STIA Banten, 2017)
One of the main functions of government is to carry out public services, namely the community who use services. Public services in the realm of regional autonomy require the implementation of prime quality public services so that all the needs of service user communities as citizens are met as stipulated in Law of the Republic of Indonesia Number 25 of 2009 Concerning Public Services. In accordance with Article 5 paragraph (1) and paragraph (2), the scope of public services includes services of public goods and public services as well as administrative services which include education, teaching, work and business, housing, communication and information, environment, health, social security, energy, banking, transportation, natural resources, tourism and other related sectors. This study aims to determine the level of satisfaction of the State Civil Apparatus (ASN) with the services of the Pandeglang Regency Regional Personnel and Education and Training Agency and to determine the weaknesses and shortcomings of each type of service it provides. This research uses a quantitative approach with descriptive explanations. The unit of analysis is Civil Servants and Contract Workers spread over 32 (thirty two) regional apparatus organizations (OPD), 35 (thirty five) sub-districts, and 1 (one) RSUD. The research instrument used a questionnaire based on the Decree of the Minister for Reform and Bureaucratic State Apparatus No. 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey. Based on the survey results, it shows that the ASN Satisfaction Index for the services of the Pandeglang Regency Regional Personnel and Education and Training Agency generally obtains a conversion interval value of 76.79, so the service quality is